Age Structure of Labour Force and Its Impact on Wages and Product - Šimková, Martina; Luboš, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Ageing of population is connected with significant changes in many areas of human life. It influences both social environment and economy, not only in the Czech Republic. Potential impact of the changes of labour force in developed countries is a subject of ongoing research in scientific community. Among all aspects, at least changes of labour productivity may appear because of changes of age structure of labour force. The issue of dependency of labour productivity on age has not been deeply discussed in the Czech Republic up to now. It is also affected by difficult availability of appropriate data. Our contribution provides the guidance how to combine different types of data. Our dataset is based on the combination of data from business statistics, statistical survey on wages and national accounts. The paper estimates the effects of age structure of labour force on level of wages and value added. It also identifies these effects both on level of total economy and particular industries for the Czech Republic between 2005 and 2015. Our findings provide additional information about population ageing to be discussed by policy makers
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 419-430
Keywords: ageing of population; average wage; gross value added; labour force